(untitled) (Research, Society and Development, 2020)
The proposal is to verify the internal control practiced by the municipalities and the role of the controllers in the exercise of their functions, seeking to understand the main challenges faced by these public agents. The objective is to analyze the functioning of the internal control system at the municipal level, from the perspective of the view of internal controllers, aiming to understand the importance of the system and professionals, for the efficient use of public resources and improving the management of public affairs. The study was applied in twenty municipalities that make up the Identity Territory of the Productive Sertão of the State of Bahia. It is an exploratory study with systematic literature review and data collection through structured questionnaires, through which the perception of internal controllers was captured and compared with technical notes from the annual accounts for the years 2016 and 2017, extracted from the electronic portal of the Court of Accounts of the Municipalities of the State of Bahia, with a sample of 100% of the population studied. The results, at first, showed that internal controllers need continuous improvement, driven mainly by the demands and dynamics imposed by the position they occupy. It was observed that there is space for the predominance of political indication over these positions, which can make the performance vulnerable. Therefore, in spite of all the evolution of the legislative framework regarding regulation and orientation of the performance of the activities of the controlling agent, it emerges to clarify the importance of this professional in the preservation of public resources, avoiding possible losses arising from errors, failures, irregularities, and in the promotion of quality management.